High-toughness high-entropy zirconate material and preparation method thereof
By using heterovalent doping method in high-entropy zirconate materials, doping Nb5+ to Zr4+ and selecting a variety of rare earth elements to form a calcined stone structure of high-entropy ceramic materials, the problem of low fracture toughness of high-entropy zirconate materials is solved, and the toughness and hardness of the material are significantly improved.
Patent Information
- Application Number
- CN202510076599.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The fracture toughness of high entropy zirconate materials is low, resulting in poor performance in CMAS erosion and foreign body damage and prone to failure.
By using the heterovalent doping method, by doping Nb5+ in Zr4+ at the B position and selecting multiple rare earth elements at the A position, the molar ratio of elements is equal, forming a calcined stone structure of high-entropy ceramic material.
It improves the fracture toughness and hardness of the material, reduces the porosity, and enhances the mechanical properties and high temperature stability of the material.
Smart Images

Figure HDA0005247280610000011 
Figure HDA0005247280610000012 
Figure HDA0005247280610000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high entropy ceramic materials, and in particular relates to a high-toughness high-entropy zirconate material and a preparation method thereof. Background Art
[0002] Thermal barrier coatings are coatings that provide thermal insulation for hot-end components such as aerospace and gas turbines. Its function is to enable materials such as gas turbines to operate for a long time under high temperature conditions to increase the corrosion resistance and thermal insulation of hot-end components, thereby extending the service life of the material. Thermal barrier coating materials generally need to have the following properties: low thermal conductivity, thermal expansion coefficient lower than zirconium, and high-temperature phase stability, etc. At present, there are many new thermal barrier coatings, such as rare earth cerates, rare earth silicates, rare earth zirconates with fluorite and pyrochlore lattice structures, and rare earth tantalates, but these materials have certain inherent performance defects, especially the fracture toughness is lower than the widely used yttria-stabilized zirconia ceramic coating. Fracture toughness represents the ability of a material to prevent crack propagation. The failure of thermal barrier coatings is usually due to crack initiation and propagation caused by thermal stress mismatch in the coating, resulting in catastrophic failure. Higher fracture toughness will ensure that the material has good performance in CMAS erosion and foreign body damage, preventing material failure. Therefore, it is necessary to study new thermal barrier coating materials with higher toughness.
[0003] In recent years, ceramic materials have been made high-entropy by introducing the concept of high entropy in high-entropy alloys. High entropy can change the chemical bonding and band structure of materials and regulate the performance of materials. High-entropy rare earth zirconates have better thermal properties than YSZ (yttria-stabilized zirconia) and are considered to be one of the candidate materials for thermal barrier coatings for hot end components of engines. It has lower thermal conductivity and good high-temperature phase stability, but its fracture toughness is lower than that of the widely used yttria-stabilized zirconia ceramic coatings. Past studies have used different elements in the A position of pyrochlore and fluorite structures to change the fracture toughness of the material, but the effect is not ideal. In view of the problem of low fracture toughness of high-entropy zirconates, providing a high-entropy rare earth zirconate ceramic material with high toughness and a preparation method thereof is of great significance for promoting the development and application of advanced ceramic materials. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of toughness of high entropy zirconate materials and to provide a high entropy ceramic material with high toughness and a preparation method thereof.
[0005] To solve the above technical problems, the present invention provides the following technical solutions: a high-toughness and high-entropy zirconate material, whose chemical formula is A2B2O7, wherein the A position is five elements of the rare earth elements La, Sm, Eu, Yb, Y, Gd, and Nd, and the molar ratio of the elements is equal, and the B position is at least one of the rare earth elements Nb and Zr, and the molar ratio of Zr and Nb is X:1-X, X=0.5~1.
[0006] Preferably, the A rare earth element is La, Sm, Eu, Yb, Y or Yb, Sm, Eu, Gd, Nd, and the molar ratio of the elements is equal.
[0007] Preferably, the B position is a rare earth element Nb or Zr, and the molar ratio of Zr to Nb is X:1-X, where X=0.5-0.6.
[0008] Preferably, the chemical formula of the high-entropy ceramic material with high toughness is: (La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2Zr2O7、(La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2(Zr 0.9 Nb 0.1 )2O7、(La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2(Zr 0.8 Nb 0.2 )2O7、(La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2(Zr 0.7 Nb 0.3 )2O7、(La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2(Zr 0.6 Nb 0.4 )2O7、(La 0.2 Sm 0.2 Eu 0.2 Yb 0.2 Y 0.2 )2(Zr 0.5 Nb 0.5 )2O7.
[0009] Furthermore, the high-toughness high-entropy zirconate material is prepared by the following steps:
[0010] Step 1: Mixing of oxide raw materials: Take metal oxides according to the proportion, mix with solvent, and perform ball milling to achieve mechanical mixing, so as to obtain slurry with corresponding proportion. Pour out the mixed slurry and put it into an oven for drying to obtain mixed raw materials, and collect the powder after sieving.
[0011] Among them, the solvent includes anhydrous ethanol, the mass ratio of the solvent to the total mass of the metal oxide is 1.5:1, the ball milling speed is set to 380 rpm, the ball milling time is 12 hours, and the ball milling beads used for ball milling have diameters of 10mm, 7mm and 5mm, corresponding to large balls, medium balls and small balls respectively. These three specifications of ball milling beads are mixed in a ratio of 2:3:1 to ensure that the powder is fully mixed. The drying temperature of the oven is set to 80℃~100℃, the drying time is 12 hours, the sieve is a 200 mesh sieve, and the mesh size of the 200 mesh standard sieve is 0.0750mm;
[0012] Step 2: The collected powder is sintered in multiple stages, and after each stage of sintering, it is mechanically activated by ball milling to obtain high entropy ceramic powder;
[0013] Among them, the sintering setting temperature is 1300-1500℃, and each sintering time is 2-4 hours. After each sintering, the powder is mixed with anhydrous ethanol solvent and ball-milled in a ball mill. Mechanical activation is achieved through repeated ball milling, which can improve the activity of the powder and reduce the sintering temperature, which is conducive to better synthesis of the sample. The ball mill speed is set to 320-400 rpm, and the ball milling time is 8-12 hours. The ball milling beads used for ball milling have diameters of 10mm, 7mm and 5mm, corresponding to large balls, medium balls and small balls respectively. These three specifications of ball milling beads are matched in a ratio of 2:3:1. The drying temperature of the oven is controlled at 80℃~100℃, and the drying time is 8-12 hours;
[0014] Step 3: Preparation of high-toughness ceramic blocks: Grind the high-entropy ceramic powder obtained in step 2, sieve it, place it in a powder tablet press, and press it to obtain a disc-shaped ceramic embryo; embed the ceramic embryo with high-entropy ceramic powder or zirconium oxide powder and place it in a muffle furnace for segmented sintering. After sintering, cool it naturally to obtain a high-toughness high-entropy ceramic material.
[0015] Among them, the sintered high-entropy ceramic powder is crushed and ground with a mortar and sieved with a 200-mesh sieve; when the desktop tablet press presses the ceramic block, the pressure is set to 10-15 MPa, and the holding time is controlled at 1.5-3 min; the powder used for embedding is the high-entropy ceramic powder or zirconia powder obtained above; the staged sintering temperature is set to 1300-1500°C, the sintering time at each temperature point is 2 hours, and the total sintering time is 6 hours.
[0016] The beneficial effects of the present invention are:
[0017] The present invention adopts a heterovalent doping method to obtain a small radius Nb 5+ Zr doped at B site 4+ The doped materials are in the same pyrochlore structure. Five elements are selected at the A position for high entropy. These five elements can keep the pyrochlore structure stable. The ion radius and atomic mass of the high entropy elements will increase the overall lattice distortion of the material, making the thermal properties of the material better.
[0018] It is difficult to achieve complete density of ceramic blocks prepared by ordinary sintering. There will be some pores. The ratio of the volume of pores to the volume of ceramics is called porosity. The increase of porosity has an adverse effect on the performance of ceramics.
[0019] After the A site is selected, a heterovalent doping is performed by Nb 5+ Doping to replace Zr 4+ , found Nb 5+ The doping of Nb will change the structure of the material. 5+ The doping will produce columnar crystals inside the material and change the porosity of the ceramic block, making the material have a smaller porosity, improving the mechanical properties of the material, and improving the toughness and hardness of the zirconate high entropy ceramic. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD diagram of the high entropy ceramic material prepared in Example 1-6;
[0021] Figure 2 SEM images of high entropy ceramic blocks prepared in Example 1(a) and Example 4(b);
[0022] Figure 3 Fracture toughness diagram of high entropy zirconate ceramic materials prepared in Examples 1, 2, 4, 6 and Comparative Examples 1-4;
[0023] Figure 4 The XRD patterns of the high entropy zirconate ceramic block prepared in Example 2.4.6 and sintered at 1500°C for 10 h were compared with those of the unsintered block; DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to specific embodiments.
[0025] The fracture toughness strength measurement method is: use a Vickers microhardness tester to test the Vickers hardness and fracture toughness of the ceramic sample. The test method is the indentation method. The surface of the ceramic sample needs to be polished before the test. Use a four-sided pyramid-shaped Vickers indenter to press an indentation on the sample surface, and calculate the fracture toughness through the indentation and crack length.
[0026] Example 1
[0027] Step 1: Mixing of oxide raw materials: La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, and ZrO2 are weighed in a molar ratio of 1:1:1:1:1:5, dispersed with anhydrous ethanol, the mass ratio of anhydrous ethanol to the total mass of the oxides is 1.5:1, and ball milling is performed. The diameters of the ball milling beads used for ball milling are 10mm, 7mm and 5mm, respectively corresponding to large balls, medium balls and small balls. The three specifications of ball milling beads are mixed in a ratio of 2:3:1. The rotation speed is 380 rpm, the ball milling time is set to 12 hours, and the mixed slurry is taken out; the slurry is sieved through a 200-mesh sieve, placed in an oven, the oven temperature is set to 100°C, the drying time is controlled to 12 hours, and after drying, it is sieved through a 200-mesh standard sieve to obtain a mixed powder;
[0028] Step 2: Place the mixed powder in a muffle furnace and sinter at 1300°C for 2 hours, cool naturally to room temperature, mix the cooled powder with anhydrous ethanol at a mass ratio of 1:1.5, and perform mechanical activation in a ball mill. The diameters of the ball milling beads used for ball milling are 10mm, 7mm, and 5mm, corresponding to large balls, medium balls, and small balls, respectively. The ball milling beads are mixed in a ratio of large, medium, and small 2:3:1. The speed is set to 380 rpm, and the ball milling time is 12 hours. After activation, place it in an oven at 100°C and dry it for 12 hours. Then sinter it at 1400°C for 2 hours, mix the powder with anhydrous ethanol at a mass ratio of 1:1.5, and perform mechanical activation (same as above). Finally, sinter the activated powder at 1500°C for 2 hours to obtain high entropy ceramic powder;
[0029] Step 3: Preparation of high-toughness ceramic blocks: Grind the high-entropy ceramic powder obtained by the final activation and sintering, pass it through a 200-mesh sieve, weigh 1.5g of powder and place it in a powder tablet press, set the pressure of the tablet press to 10MPa, hold the pressure for 2min, and press to obtain a disc-shaped ceramic embryo; coat the ceramic embryo with zirconium oxide powder and place it in a muffle furnace for staged sintering, keep it warm at 1300, 1400, and 1500°C for two hours respectively, and then cool it down naturally to obtain a high-toughness high-entropy ceramic material block.
[0030] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase;
[0031] Figure 2 This is a SEM image of the high entropy ceramic block prepared in this embodiment. It can be seen from the image that the high entropy ceramic block has obvious grain boundaries;
[0032] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 1.65 MPa·m 1 / 2 By comparing with the comparative example, it can be seen that the fracture toughness of the material is not much different from that of the comparative example.
[0033] Embodiment 2:
[0034] The difference between Example 2 and Example 1 is that step 1 is to weigh seven oxides of La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, ZrO2 and Nb2O5 in a molar ratio of 1:1:1:1:1:4.5:0.5 and disperse them with anhydrous ethanol, and the remaining steps are the same as Example 1.
[0035] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase.
[0036] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 1.75 MPa·m 1 / 2 By comparing with Example 1 and the comparative example, it can be seen that the fracture toughness of the material is better than the original strength without aliovalent doping.
[0037] Figure 4 The XRD spectrum comparison diagram of the prepared high entropy zirconate ceramic block sintered at 1500°C for 10 hours and the unsintered one shows that the ceramic material prepared in this embodiment can still maintain the original structure after sintering at 1500°C for 10 hours, and has excellent high-temperature stability.
[0038] Embodiment 3:
[0039] The difference between Example 3 and Example 1 is that step 1 is to weigh seven oxides of La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, ZrO2 and Nb2O5 in a molar ratio of 1:1:1:1:1:4:1 and disperse them with anhydrous ethanol, and the remaining steps are the same as Example 1.
[0040] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase;
[0041] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 1.92 MPa·m 1 / 2 By comparing with the previous embodiments and comparative examples, it can be seen that the fracture toughness of the material is improved compared with the case of aliovalent doping.
[0042] Embodiment 4:
[0043] The difference between Example 4 and Example 1 is that step 1 is to weigh seven oxides of La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, ZrO2 and Nb2O5 in a molar ratio of 1:1:1:1:1:3.5:1.5 and disperse them with anhydrous ethanol, and the remaining steps are the same as Example 1.
[0044] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase;
[0045] Figure 2 This is a SEM image of the high entropy ceramic block prepared in this embodiment. It can be seen from the image that many fine columnar crystals are generated at the grain boundaries of the high entropy ceramic block;
[0046] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 2.12 MPa·m 1 / 2 By comparing with the previous examples and comparative examples, it can be seen that the fracture toughness of the material is improved compared with the case of alivalent doping;
[0047] Figure 4The XRD spectrum comparison diagram of the prepared high entropy zirconate ceramic block sintered at 1500°C for 10 hours and the unsintered one shows that the ceramic material prepared in this embodiment can still maintain the original structure after sintering at 1500°C for 10 hours, and has excellent high-temperature stability.
[0048] Embodiment 5:
[0049] The difference between Example 5 and Example 1 is that step 1 is to weigh seven oxides of La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, ZrO2 and Nb2O5 in a molar ratio of 1:1:1:1:1:3:2 and disperse them by anhydrous ethanol, and the remaining steps are the same as Example 1.
[0050] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase;
[0051] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 2.46MPa·m 1 / 2 By comparing with the previous examples and comparative examples, it can be seen that the fracture toughness of the material is improved compared with the case of alivalent doping;
[0052] Embodiment 6:
[0053] The difference between Example 6 and Example 1 is that step 1 is to weigh seven oxides of La2O3, Sm2O3, Eu2O3, Yb2O3, Y2O3, ZrO2 and Nb2O5 in a molar ratio of 1:1:1:1:1:2.5:2.5 and disperse them with anhydrous ethanol, and the remaining steps are the same as Example 1.
[0054] Figure 1 The XRD diffraction spectrum of the ceramic material prepared in this embodiment detected characteristic peaks (311), (331), and (511) of the pyrochlore structure, so the high entropy ceramic material is a pyrochlore phase;
[0055] from Figure 3 It can be seen that the fracture toughness strength of the ceramic block synthesized by this embodiment is 2.96MPa·m 1 / 2 By comparing with the previous examples and comparative examples, it can be seen that the fracture toughness of the material is improved compared with the case of alivalent doping;
[0056] Figure 4The XRD spectrum comparison diagram of the high entropy zirconate ceramic block sintered at 1500°C for 10 hours and the unsintered one is shown. The ceramic material prepared in this embodiment can still maintain the original structure after sintering at 1500°C for 10 hours, and has excellent high-temperature stability.
[0057] Comparative Example 1:
[0058] The difference between Comparative Example 1 and Example 1 is that in step 1, La2O3 and ZrO2 are weighed in a molar ratio of 1:2, dissolved in anhydrous ethanol, the mass ratio of ethanol to powder is 1.5:1, and ball milled. The remaining steps are the same as in Example 1.
[0059] Depend on Figure 3 From the fracture toughness spectrum corresponding to Comparative Example 1, it can be seen that the fracture toughness of the ceramic prepared in this comparative example is 1.39 MPa·m 1 / 2 Compared with other embodiments and comparative examples, the mechanical properties of the block prepared in comparative example 1 are poor.
[0060] Comparative Example 2:
[0061] The difference between Comparative Example 2 and Example 1 is that, in step 1, La2O3, Sm2O3, Eu2O3, Gd2O3, Nd2O3 and ZrO2 are weighed in a molar ratio of 1:1:1:1:1:5, dissolved in anhydrous ethanol, the mass ratio of ethanol to powder is 1.5:1, and ball milling is performed. The remaining steps are the same as in Example 1.
[0062] Depend on Figure 3 From the fracture toughness spectrum corresponding to Comparative Example 2, it can be seen that the fracture toughness of the ceramic prepared in this comparative example is 1.33 MPa·m 1 / 2 Compared with other embodiments and comparative examples, the mechanical properties of the block prepared in comparative example 2 are also poor.
[0063] Comparative Example 3:
[0064] The difference between Comparative Example 3 and Example 1 is that in step 1, Yb2O3, Sm2O3, Eu2O3, Gd2O3, Nd2O3 and ZrO2 are weighed in a molar ratio of 1:1:1:1:1:5, dissolved in anhydrous ethanol, the mass ratio of ethanol to powder is 1.5:1, and ball milling is performed. The remaining steps are the same as in Example 1.
[0065] Depend on Figure 3 From the fracture toughness spectrum corresponding to Comparative Example 3, it can be seen that the fracture toughness of the ceramic prepared in this comparative example is 1.78 MPa·m 1 / 2 .
[0066] Comparative Example 4:
[0067] The difference between Comparative Example 4 and Example 1 is that in step 1, La2O3, Nd2O3, Eu2O3, Gd2O3, ZrO2, and HfO2 are weighed in a molar ratio of 1:1:1:1:2:2, dissolved in anhydrous ethanol, the mass ratio of ethanol to powder is 1.5:1, and ball milling is performed. The remaining steps are the same as in Example 1.
[0068] Depend on Figure 3 From the fracture toughness spectrum corresponding to Comparative Example 4, it can be seen that the fracture toughness of the ceramic prepared in this comparative example is 1.63 MPa·m 1 / 2 Compared with other embodiments and comparative examples, the mechanical properties of the blocks prepared in comparative example 4 are improved compared with the comparative examples, but are still worse than those of the embodiments.
[0069] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A high-toughness high-entropy zirconate material, characterized in that: The chemical formula of the high entropy ceramic material is A2B2O7, wherein A is five elements of the rare earth elements La, Sm, Eu, Yb, Y, Gd, and Nd, and the molar ratio of the elements is equal, and B is at least one of the rare earth elements Nb and Zr, and the molar ratio of Zr and Nb is X:1-X, where X=0.5~1.
2. The high-toughness high-entropy zirconate material according to claim 1, characterized in that: The A rare earth elements are La, Sm, Eu, Yb, Y or Yb, Sm, Eu, Gd, Nd, and the molar ratio of the elements is equal.
3. A method for preparing a high-toughness high-entropy zirconate material according to claim 1 or 2, characterized in that: The preparation method steps are as follows: Step 1: taking metal oxides according to a certain proportion, mixing them with a solvent, ball milling, drying, sieving and collecting; Step 2: The collected powder is sintered in multiple stages, and after each stage of sintering, it is mechanically activated by ball milling to obtain high entropy ceramic powder; Step 3: Grind and sieve the high entropy ceramic powder obtained in step 2, press it into tablets, embed it, and sinter it in multiple stages to prepare a high entropy ceramic block.
4. The method for preparing a high-toughness high-entropy zirconate material according to claim 3, characterized in that: The solvent in step 1 is anhydrous ethanol; the mass ratio of the solvent to the total mass of the metal oxide is 1.5:
1.
5. The method for preparing the high-toughness high-entropy zirconate material according to claim 3, characterized in that: The ball milling speed in step 1 is 320-400 rpm for 12 hours.
6. The method for preparing the high-toughness high-entropy zirconate material according to claim 3, characterized in that: The multi-stage sintering temperature in step 2 is 1300-1500° C., and the sintering time for each stage is 2-4 hours; the ball milling speed in step 2 is set to 320-400 rpm, and the ball milling time is 8-12 hours.
7. The method for preparing the high-toughness high-entropy zirconate material according to claim 3, characterized in that: The tableting in step 3 uses a powder tablet press with a pressure of 10 to 15 MPa and a holding time of 1.5 to 3 minutes.
8. The method for preparing the high-toughness high-entropy zirconate material according to claim 3, characterized in that: The embedding in step three uses the high entropy ceramic powder or zirconium oxide powder obtained in step two.
9. The method for preparing the high-toughness high-entropy zirconate material according to claim 3, characterized in that: The segmented sintering temperature in step three is 1300° C. to 1500° C., the sintering time of each segment is set to 2 hours, and the cumulative sintering time is 6 hours.
Citation Information
Patent Citations
High-entropy ceramic powder used for thermal barrier coating and preparation method of ceramic powder
CN110272278A
Pyrochlore type high-entropy oxide solidified body and preparation method thereof
CN111533557A
Low-thermal-conductivity high-entropy ceramic thermal barrier coating material
CN114149260A
Low-thermal-conductivity CMAS-corrosion-resistant high-entropy zirconate ceramic material as well as preparation method and application thereof
CN115925417A
High-entropy ceramic thermal barrier coating and preparation method thereof
CN116377372A